Buy-o-logy of Indians: A Cultural Model of Studying Consumer Behaviour - Renu Isidore; C. Joe Arun (STIE Malangkucecwara, 2022)
Every product is a cultural product and every buying is a cultural buying and therefore it is a cultural relationship between the consumer and the product. A consumer views the product from a worldview born out of different cultural practices that give birth to habits. The consumer uses a particular language to explain his/her worldview. In the process of relationship between the product and consumer, the consumer gives meaning to the product that he/she buys. Once the product is bought and consumed, the meaning he/she had given provides now a sense of fulfilment, a meaning to the consumer’s life that we call it cognitive resonance. If the product does not give the sense of satisfaction, it will cause a cognitive dissonance that makes the consumer dispose the product. Hence when we study the consumer behaviour, we need to focus on (1)the worldview that is born out of (2)culture, and expressed in (3)a language and the (4)relationship the consumer has with the product in the process of buying. In the entire process, the cultural worldview gives the consumer an agency, what we call human agency, to decide when, where why and what to buy. This paper suggests a way to study consumer behaviour from a cultural perspective.